PENILAIAN KINERJA KARYAWAN PADA BANARAN 9 HOTEL &RESORT MENGGUNAKAN METODE FUZZY LOGIC - Naniek Utami Handayani; Satrio Arifianto (Performa: Media Ilmiah Teknik Industri, 2015)
To improve the performance of human resources effectively and efficiently, there needs a performance assessment system to benchmarks of success in human resource development. The performance assessment system should be able to assess the ability of employees to carry out their tasks and responsibilities and became the basis of reward and punishment system. Performance assessment system of employee in Banaran 9 Hotel & Resort is a form of evaluation work. The performance assessment only assess aspects of the work, work attitudes and job skills. However, it is still subjective of assessment system. The manager could assess the work of each employee based on like and dislike because there are no clear indicators of performance assessment. On the other hand, the level of turnover Banaran 9 Hotel & Resort is quite high. This research objective is to develop an objective system of performance assessment to support the achievement of corporate goals. The method used in this research is fuzzy AHP and fuzzy logic. The results showed the highest rank earned by the employees with the code E26, which means that the employee is eligible to be promoted or given rewards according to his performance and achievements